Examples
Example 2 (i)
Example 2 (ii) Important
Example 3 You are here
Example 4
Example 5 Important
Example 6 (i)
Example 6 (ii) Important
Example 7 Deleted for CBSE Board 2022 Exams
Example 8 Important Deleted for CBSE Board 2022 Exams
Example 9
Example 10
Example 11 Important
Example 12
Example 13 (i) Important Deleted for CBSE Board 2022 Exams
Example 13 (ii) Deleted for CBSE Board 2022 Exams
Example 14 Important
Example 15
Example 16 Important Deleted for CBSE Board 2022 Exams
Examples
Last updated at May 29, 2018 by Teachoo
Example 3 Express (5 – 3i)3 in the form a + ib. (5 – 3i)3 It is of the form (a – b)3 Using (a – b)3 = a3 - b3 – 3ab (a – b) Putting a = 5, b = 3i The above equation becomes (5 – 3 i)3 = 53 – (3i)3 – 3 × 5 × (3i) (5 – 3 i) = 125 – 27 i3 – 45i (5 – 3i) = 125 − 27 i × (i2) – 45 i × (5) + 45 i × (3 i) = 125 − 27 i (i2) – 225 i + 135(i2) = 125 − 27 i (−1) – 225 i + 135(–1) = 125 + 27 i – 225 i – 135 = 125 – 135 + i (27 – 225) = – 10 + i (–198) = – 10 – i 198